A Behavioral Theory of Policy Feedback in Tobacco Control: Evidence From a Difference‐In‐Difference‐In‐Difference Study. Issue 2 (24th October 2018) - Vannoni, Matia
Abstract : Public policy scholars argue that in highly tangible policies, such as tobacco control, the public learns from the direct experience of the beneficial effects of the policy. Empirical evidence supports this argument, suggesting that in the United States the introduction of tobacco control measures makes people more inclined to further regulation. By relying on a set of cases which allows testing the effects of the introduction of tobacco control measures across European countries on a series of relevant variables, this study confirms that the introduction of tobacco control measures makes the public more inclined to further regulation. Yet, when the effects of these policies are disaggregated between smokers and nonsmokers, results show that these positive effects are driven by smokers. This puzzle suggests that different effects than mass attitudinal policy feedback effects, driven by learning from direct experience, might explain the positive reaction to tobacco control. This study puts forward a behavioral theory of policy feedback, which suggests that smokers react positively to the introduction of tobacco control measures because they see these measures as commitment devices, which can help them quit smoking. Evidence for this argument is found by demonstrating that the introduction of tobacco control measures increases smokers' welfare.